Development of Integrated Teaching in Primary Education in the Republic of Poland - BinytskaКateryna (Pedagogical Discourse, 2017)
The article deals with the problem of the development of integrated teaching in primary education in the Republic of Poland. The views of Polish teachers on the question of integrated teaching in primary education have been studied. The article examines the development of primary education of the Republic of Poland in the period of 1945-1999. The Polish legal documents regulating and controlling the activity of primary schools in the country have been analyzed. It is mentioned that in the 1960-s integration of teaching in primary education (in grades I to IV) could be of various degrees. It is accentuated that in the 70-s of the twentieth century the subject system and integrated teaching in Polish primary education functioned in parallel. It is reported that in 1980, in connection with the economic crisis in the country, the abandonment of the structural reform of school was announced. At the beginning of 90-s of the twentieth century the processes of democratization, which took place in the primary level of education were observed in the country. Since 1999, the country has begun educational reform, which envisaged the introduction of a six-year primary school that includes two stages of training. The first stage: I-III classes – integrated primary education. Modern integrated teaching in the I-III classes is a smooth transition from pre-school education to primary education in the school’s educational system. The benefits of the integrated teaching in primary education have been defined. The views of Polish scholars have been indicated that the system of classroom education under the modern conditions is obsolete and significantly impedes the development of autonomy and activity of pupils and was adapted mainly to the talents of gifted pupils. Such a system of teaching gives all children the same requirements, regardless of their individual peculiarities of development, imposes the same pace of work, not taking into account the different levels of abilities development, interests and needs of pupils. The classroom system is worked out to provide pupils with encyclopaedic knowledge and rarely provides the opportunity to use the gained knowledge in life situations. It is generalized that the study of Polish experience in implementing integrated teaching in primary education will help to understand the essence of this innovation in the domestic primary school.